P14: DISCONTINUATION AND NON-PUBLICATION OF SURGICAL RANDOMISED CONTROLLED TRIALS IN THE SETTING OF ILEUS: OBSERVATIONAL STUDY. (27th April 2021) - Helliwell, JA; Chapman, SJ; Jayne, DG
Abstract: Introduction: Once regarded as an inevitable occurrence after surgery, ileus is now recognised as an unmet clinical need. Despite this, few studies have shown meaningful clinical benefit which may be due to the challenges associated with conducting trials in this setting. The aim of this study was to determine the rate of discontinuation and non-publication of randomised controlled trials (RCTs) in the setting of ileus. Method: A systematic search of ClinicalTrials.gov was performed using the keyword "ileus". RCTs registered between 2003-2019 involving abdominal surgery were eligible. Studies were divided according to completion status. Authors were contacted to seek information about the circumstances for discontinuation and non-publication. For completed studies, evidence of a published manuscript was sought. Result: Of 262 trials identified, 81 were eligible for analysis. Amongst 27 discontinued trials, email addresses were identified for 24 (88.9%) and replies received from 6 (25.1%). The most common reasons for discontinuation were loss of clinical significance (n=2) and insufficient recruitment (n=2). Amongst 54 completed studies, manuscripts were identified for 34 (63.0%). Of these, email addresses were identified for 12 (60.0%) and replies received from 5 (41.7%). The most common reason for non-publication was a lack of time/resources/personnel (n=3). Conclusion: One third of trials undertaken were discontinued and of those which did reach completion, less than two thirds reported results. A lack of resources and loss of clinical significance were predominant reasons. There is an urgent need to address methodological barriers in research relating to ileus to promote rigorous evaluation of new treatments. Take-home message: One third of trials undertaken were discontinued and of those which did reach completion, less than two thirds reported results. A lack of resources and loss of clinical significance were predominant reasons. There is an urgent need to address methodological barriers in research relating to ileus to promote rigorous evaluation of new treatments.